Exploring factors hindering performance of information systems in the South African public sector – evidence from the Zondo Commission - Ashley Latchu; Shawren Singh (Системный анализ и прикладная информатика, 2024)
This article seeks to ascertain issues in the Commission of Inquiry popularly known as the Zondo Commission that consequently hinder and impede the performance of information systems in the South African public sector. The novelty of this study lies in its thematic perspective on factors that disrupts the public sector from attaining objectives that are spelt out in the South African national strategic goals. Zondo commission final reports are used to explore intrinsic aspects which could explain current threats to information systems. The Zondo Commission covered the period from 2018 to 2022 and reports are available on the State Capture Commission website. The study employs a qualitative research approach by analysing data from the Zondo Commission reports. A qualitative software, Atlas.ti 9 is utilised to demystify macro factors thwarting information systems from operating efficiently and effectively. The usage of the standard software package Atlas.ti 9 is for the purpose of automating the coding procedures for this study by employing specified rules to enable promptness and efficiency in handling vast amounts of textual data, as well as organise, filter, and sort that data. In order to provide direction for this automated analysis, a coding schema is used that identifies the codes or keywords that should be looked for within the text, and should be based on an initial human evaluation of the sample textual data. The textual codes are arranged into relatively high codes or constructions. The coding schema is tested by employing a separate sample of texts in order to check for accuracy and adequateness. The emerging themes from the thematic analysis showed that destabilisation of the public entities’ business systems and structures, non-penalisation of offenders, overstating of tender values and lack of goal congruency were the main reason that affected performance of information systems. The study recommends that government employ robust procurement and monitoring systems.